Effect of microtexturing on tribological performance of Ni/Ni–SiC composite coatings. (September 2015) - Gyawali, G.; Joshi, B.; Tripathi, K.; Kim, S.-H.; Wohn Lee, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Laser surface texturing is one of the promising surface modification techniques to reduce wear and friction properties of materials. In this study, we report the comparative effect of laser surface texturing on commercial nickel, electrodeposited nickel and Ni–SiC composite coatings. Hemispherical dimples, with 80–200 μm dimple spacing, were created and examined on the surfaces of the materials studied. The results revealed that microsurface texturing with 150 μm dimple spacing considerably improved the coefficient of friction. Electrodeposited nickel has shown improved coefficient of friction under identical texturing and tribological conditions when compared to commercial nickel. Furthermore, incorporation of SiC nanoparticles in nickel, by codeposition processes, resulted in the increase in microhardness of the coating, which in turn prevented the dimples from being deformed after wear testing. Dimple spacing accuracy and incorporated second phase ceramic particles both contributed significantly to reduction in coefficient of friction of electrodeposited Ni–SiC composite coatings.